2009
DOI: 10.1002/ddr.20331
|View full text |Cite
|
Sign up to set email alerts
|

Tat‐mediated peptide intervention in analgesia and anesthesia

Abstract: Membrane-permeable peptide carriers are attractive drug delivery tools. Among such carriers, the protein transduction domain (PTD) of the human immunodeficiency virus-type 1 Tat protein is most frequently used and has been successfully shown to deliver a large variety of cargoes. The Tat PTD can facilitate the uptake of large, biologically active molecules into mammalian cells, and recent studies have shown that it can mediate the delivery of different cargoes into tissues throughout a living organism. Given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Short in vivo half-life has been a general challenge for TAT-conjugated drugable small interfering peptides (designated as peptide aptamers), 18 , 19 , 20 including TAT-CBD3, which is unstable and produces only transient pain relief. 10 Scaffold proteins such as GFP have been successfully used to provide a framework for the expression stable peptide aptamers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short in vivo half-life has been a general challenge for TAT-conjugated drugable small interfering peptides (designated as peptide aptamers), 18 , 19 , 20 including TAT-CBD3, which is unstable and produces only transient pain relief. 10 Scaffold proteins such as GFP have been successfully used to provide a framework for the expression stable peptide aptamers.…”
Section: Resultsmentioning
confidence: 99%
“…A number of synthetic peptide inhibitors, including CBD3 conjugated to the TAT motif, have shown efficacy for pain caused by various pathological conditions, 9 , 28 , 29 and systemic administration of TAT-mediated analgesic peptides has been proposed as a promising alternative approach for the treatment of chronic pain. 20 , 30 However, this strategy also has some limitations, including the inability to target specific organs or cells. Another major obstacle in using TAT as a delivery vector is its rapid clearance when administrated in vivo , resulting in total clearance in as rapidly as 2 h after a bolus tail vein injection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comprehensive toxicity studies including cell viability, proliferation and leakage of lactate dehydrogenase showed no toxic effects of TAT compared to other PTDs . Other advantages of TAT are its high transduction efficiency, little perturbation to the plasma membrane and its ability to transfer the blood–brain barrier , which is necessary for the treatment of MMA pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Key features of nanoparticles such as versatile composition, unique physical properties, passive targeting abilities, as well as tunable surface functionality for active targeting, enable the transportation of diagnostic or therapeutic agents across the BBB [20] . Another alternative is to employ membrane-permeable peptide carriers, usually oligopeptides that can rapidly cross the plasma membrane, even the BBB and deliver a range of bioactive molecules to the cytoplasm or nucleus, to mediate in vivo delivery of the complex [21] . Some problems such as pharmacokinetics and toxicity of 188 Re-labeled U2 upon systemic delivery are worthy of detailed research.…”
Section: Discussionmentioning
confidence: 99%